The role of middle ear risk index on the outcome of surgery for chronic otitis media - Bothra, Jitendra; Swami, Himanshu; Sahu, Pankaj Kumar; Goyal, Lovraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Chronic otitis media (COM) is a highly prevalent disease of the middle ear and constitutes a serious health problem worldwide, especially in developing countries. This study was done to evaluate the role of the middle ear risk index (MERI) on the outcome of surgeries for COM in the form of successful graft uptake and improvement in hearing. Methods: A total of 68 patients of COM were included in this study. Detailed ENT examination and preoperative pure tone audiometry were done in all patients. MERI score was calculated and patients were stratified based on the MERI score. All patients were evaluated at the end of 3 months postoperatively, for the status of graft uptake and improvement in hearing. Results: The MERI was found to be a remarkable predictor of the outcome of surgeries for COM. The patients with mild MERI scores had a significantly better prognosis than patients with severe MERI scores. Conclusions: MERI is a very useful and honest predictor of the graft uptake and hearing benefit in patients undergoing surgeries for COM. It has an inverse relation with graft uptake and hearing beneﬁt. Based on the MERI score, the likelihood of surgical success and hearing beneﬁt could be explained to the patient of COM to give them realistic expectations.